2018
DOI: 10.1111/1747-0080.12399
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with fruit and vegetable and total fat intake in university students: A cross‐sectional explanatory study

Abstract: Future interventions aiming to improve dietary intake among university students should focus on younger students with lower socioeconomic status and should enhance students' subjective norm and behavioural control concerning healthy eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
6
19
0
Order By: Relevance
“…In addition, their study showed that this difference in fruit intake is explained by diet status and health beliefs. This assertion is corroborated by several other studies [22,23]. Again, more females consumed carbohydrate-rich foods such as rice (50.3%), maize (50.4%), cassava (51.1%) and yam (52.6%) than the male population subgroup ( Figure 2).…”
Section: Study Protocolsupporting
confidence: 82%
“…In addition, their study showed that this difference in fruit intake is explained by diet status and health beliefs. This assertion is corroborated by several other studies [22,23]. Again, more females consumed carbohydrate-rich foods such as rice (50.3%), maize (50.4%), cassava (51.1%) and yam (52.6%) than the male population subgroup ( Figure 2).…”
Section: Study Protocolsupporting
confidence: 82%
“…The literature review highlighted the difficulty in reaching and engaging young adults to change their lifestyle behaviors [13]. It was also highlighted that undertaking university study is a key experience for many young adults [15,16] and that unhealthy eating behaviors are also characteristic of young adults who attend university [25,26]. It was based on these findings that the target population was further refined to include young adult (17 to 35 years) university students.…”
Section: Methodsmentioning
confidence: 99%
“…Unhealthy diets are typical of university students, including low intakes of fruit and vegetables and high intakes of energy‐dense nutrient poor (EDNP) foods, such as takeaway foods and sugar‐sweetened drinks . These unhealthy diets are linked with a range of negative health effects, including poorer mental health, weight gain and other risk factors for chronic disease .…”
Section: Introductionmentioning
confidence: 99%